TB SCREENING IN HIV- INFECTED PRISONERS, RELEASED PRISONERS AND HOMELESS PERSONS IN A MULTI-CENTRE COHORT STUDY IN THE NORTH-WEST REGION OF RUSSIA - Z. M. Zagdyn; T. I. Danilova; N. Yu. Kovalev; A. Yu. Kovelenov; N. A. Belyakov; A. Rumman; R. Rumman; A. Sadeghi; D. Cox; J. Pankovich; R. Rosenes; C. Cooper; et al. (Журнал инфектологии)
The aim: of the prospective cohort study was a TB screening evaluation in HIV-infected current and released prisoners and homeless people in comparison to the local HIV-infected residents in the pilot territories. Methods: Prospective data collection of newly registered HIV and TB co-infected cases was provided inSt. Petersburg,VologdaandLeningradregions between 2008 and 2011. The patients’ social and demographic, clinical and epidemiological characteristics were analyzed and predictors of TB-attributable mortality were evaluated. Results: A total of 2888 patients were included in the analysis: 1570 local residents, 777 released prisoners, 404 prisoners and 137 homeless persons. There was no significant difference in age, but prisoners, released prisoners and homeless persons were more likely to be male, urban resident, unemployed and injection drug user, less likely to have microbiological confirmation, presented with a greater incidence of disseminated lung TB, lower CD4 cell count. Significant predictors of TB-attributable morality were current or prior incarceration, urban residence, unemployment, symptoms lasting over 1 year, extra-pulmonary TB at presentation and CD4 cell count less than 200 cell/mkl. Conclusions: Found TB cases in HIV-infected prisoners, released prisoners and homeless persons were at a significantly more advanced disease stage and presented with greater morbidity and mortality to compare to the local residents. Targeted early screening and on time started treatment interventions could improve TB outcomes in these highly vulnerable social groups.